Optimizing Online Advertising to Improve J&T Cargo's Business Performance and Profitability - Aryani, Kiki; Rahayu, Agus; Hendrayati, Heny (International Journal of Science and Society, 2024)
The optimization of online advertising has become a key strategy for improving business performance and profitability in the digital era. This study aims to analyze the role of online advertising in supporting the growth of J&T Cargo's business using a qualitative approach with a literature review method. Through a review of relevant literature, the research explores the effectiveness of various digital advertising platforms, such as social media, search engines, and e-commerce websites, in reaching wider audiences and increasing customer conversion rates. The findings reveal that implementing the right online advertising strategies can enhance brand awareness, expand market share, and boost profitability. This study offers recommendations for J&T Cargo to optimize data-driven advertising strategies to achieve better business outcomes.